Status of the stateless population in Thailand: How does stigma matter in their life? - Siwarak Kitchanapaibul; Tawatchai Apidechkul; Peeradone Srichan; Thanatchaporn Mulikaburt; Onnalin Singkhorn; Anusorn Udplong; Panupong Upala; Chalitar Chomchoei; Fartima Yeemard; Ratipark Tamornpark; Pilasinee Wongnuch (PLoS ONE, 2022)
Background The stateless population in Thailand live by accessing all public services, including the health care system. Stigma is a crucial factor impacting these individuals' lives and their access to medical care. This study aimed to understand the experience of the stateless population in Thailand and how they overcome the problem of stigma. Methods A qualitative method was used to elicit information from key informants who were members of the stateless population, which was classified as those who did not hold Thai identification cards (IDs). A questionnaire was used to guide the interview, which was conducted in a private and confidential room. The interviews were conducted after voluntary agreement was obtained from the participants; each interview was held in August 2021 and lasted for approximately 45 minutes. Results Fifty-one people participated in the study; 68.6% were females, 86.3% were married, and 90.2% were Akha or Lahu. The stateless population in Thailand reported four types of perceived stigma: having a lower ability to request that their needs be met, not being equal to others, not being able to qualify for health care services and being ranked below other hill tribe people who have IDs. The phrase "life is nothing" was presented by the participants, who reported that they felt like an invisible population in Thailand. Some participants reported that other hill tribe people who have IDs act as stigma perpetuators among members of the stateless population who do not have IDs. Maintaining their privacy within their village, trying to obtain a Thai ID, and practicing the Thai language were the main ways of avoiding the stigma reported by the stateless population. Obtaining a Thai ID was detected as the top goal in their aim to overcome the stigma problem. Conclusions The stateless population in Thailand live as an invisible population and are negatively treated via various patterns from others. Accessing Thai IDs and education are argued to be the most effective procedures for addressing the problem under the implementation schemes of the relevant organizations.